Reliability of Measuring Instability of the Knee in Anterior Cruciate Ligament Injury Patients and Its Application to Evaluation in the Physical Therapy - ABE, HITOSHI; UCHIYAMA, YASUSHI; GUNJI, AKIRA (Rigaku ryoho kagaku, 1999)
We performed quantitative measurements of knee instability on 26 persons with anterior cruciate ligament injuries as subjects, with the objective of clarifying factors affecting feeling of instability at the time of motion in anterior cruciate ligament injury patients. The reliability and relationships between each of the indices were investigated and compared with muscle strength and knee instability judged from subjective symptoms at time of motion. For the knee instability, intra-class correlation coefficients above 0.8 were obtained, and in the relationship between each of the indices the correlation between tibial displacement and stiffness was high, although the changes of both were not uniform, and for knee instability a qualitative evaluation was thought necessary. Also, when the factors of feeling of instability were looked at from the point of view of muscle strength and knee instability, in knee instability there was a significant difference between stiffness and displacement at the time of a 133N load, and for muscle strength there were significant differences among the extensor muscles at low velocities.